Improving Student Text Writing Ability by Utilizing the Use of Augmented Reality Feature - Fitria Meisarah; Cut Susan Octiva; Purwo Agus Sucipto; Ika Rahayu Satyaninrum; Asri Ady Bakri (SEULANGA SYSTEM PUBLISHER, 2023)
This study used a quantitative methodology. Experimental research is used, with a post-test-only control design as the study design. There were 100 students in the study's population, and students from classes A (the experimental type) and C (the control class) made up the sample. This study uses assemblers as a learning medium applied to those classes. Two variables are used in this study: the independent variable (the augmented reality feature in the assembler application) and the dependent variable (the ability to write descriptive texts for class students). Data collection techniques used are interview techniques, documentation, and observation. The application used to process research data is SPSS. This study's results show an influence between using augmented reality features and students' writing abilities. This is evident from the average value of the experimental class and control class.